1993
DOI: 10.1111/j.1755-3768.1993.tb04987.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation syndrome: Clinical factors related to capsular rupture in cataract surgery

Abstract: Extracapsular surgery has a high frequency of capsular rupture or disinsertion in patients with pseudoexfoliation syndrome. Irido-phakodonesis is one of the factors that suggests this complication. Irido-phakodonesis acts as an 'all or nothing' mechanism, as it does not appear until there is a certain degree of zonular lesion. We carried out a study on 330 eyes with pseudoexfoliation, relating irido-phakodonesis to 31 clinical signs. The results showed that irido-phakodonesis is related to cataracts, degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 8 publications
0
26
0
3
Order By: Relevance
“…1,2 PEX is linked to glaucoma and has a higher rate of intraoperative and postoperative complications during cataract surgery. [3][4][5] Both undilated and dilated slit-lamp biomicroscopy are used during the clinical examination to detect the white dandruff like material on the pupil, lens, and the angle, as well as other signs such as parapupillary transillumination defects. 6,7 PEX is not only an ocular disease, but also a generalized disorder that involves the abnormal production and/or turnover of extracellular matrix material.…”
mentioning
confidence: 99%
“…1,2 PEX is linked to glaucoma and has a higher rate of intraoperative and postoperative complications during cataract surgery. [3][4][5] Both undilated and dilated slit-lamp biomicroscopy are used during the clinical examination to detect the white dandruff like material on the pupil, lens, and the angle, as well as other signs such as parapupillary transillumination defects. 6,7 PEX is not only an ocular disease, but also a generalized disorder that involves the abnormal production and/or turnover of extracellular matrix material.…”
mentioning
confidence: 99%
“…1 Cataract surgery in patients with pseudoexfoliation is associated with a statistically higher incidence of intraoperative and postoperative complications including vitreous loss, capsule rupture, zonule rupture, and pseudophakodonesis. [2][3][4][5][6][7][8] Delayed dislocation of the IOL has been reported, with subsequent need for surgical correlation. 9,10 This may be because eyes with pseudoexfoliation are noted to have weaker zonules and/or weaker lens capsules.…”
Section: Discussionmentioning
confidence: 99%
“…[9] The amount of exfoliative material in the zonules is not predictive of intra-operative zonule weakness. [10] The ages of patients diagnosed with PXE in this study were 60-80 years age group. Epidemiological studies of PXE have shown that it is more common in patients older than 60 years and prevalence further increases with age.…”
Section: Discussionmentioning
confidence: 99%